2023
DOI: 10.1183/16000617.0170-2023
|View full text |Cite
|
Sign up to set email alerts
|

Nine controversial questions about augmentation therapy for alpha-1 antitrypsin deficiency: a viewpoint

Marc Miravitlles,
Antonio Anzueto,
Miriam Barrecheguren

Abstract: Augmentation therapy with intravenous alpha-1 antitrypsin is the only specific treatment for alpha-1 antitrypsin deficiency (AATD)-associated emphysema. This treatment has been available and remained basically unchanged for more than 35 years, but many questions persist regarding its indications, regimen of administration and efficacy. Because AATD is a rare disease, it has not been possible to conduct randomised, placebo-controlled trials that are adequately powered for the usual outcomes analysed in non-AATD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…According to the above, these preliminary results should encourage further well-designed studies and support the systematic investigation of AATD with an active case search through screening in all patients clinically suspected of being carriers of deficiency alleles and in relatives of the index cases, to reduce the current underdiagnosis and to offer those diagnosed the benefits of an early diagnosis. Early detection of new cases is important because undiagnosed AATD can have a very negative impact on the health of patients [30], and even in those treated late, although augmentative treatment can delay the loss of lung density, it does not recover the lost lung tissue, so it is necessary to begin treatment, if indicated, as soon as possible [31]. In 1997, the World Health Organization and, subsequently, practically all scientific societies recommended investigating AATD in all patients with COPD and in blood relatives of the index cases, as well as in other pathologies related to AATD, including bronchiectasis of unknown cause, neonatal cholestasis, liver cirrhosis of unknown cause, granulomatous polyangiitis, and neutrophilic panniculitis [1,2,32].…”
Section: Discussionmentioning
confidence: 99%
“…According to the above, these preliminary results should encourage further well-designed studies and support the systematic investigation of AATD with an active case search through screening in all patients clinically suspected of being carriers of deficiency alleles and in relatives of the index cases, to reduce the current underdiagnosis and to offer those diagnosed the benefits of an early diagnosis. Early detection of new cases is important because undiagnosed AATD can have a very negative impact on the health of patients [30], and even in those treated late, although augmentative treatment can delay the loss of lung density, it does not recover the lost lung tissue, so it is necessary to begin treatment, if indicated, as soon as possible [31]. In 1997, the World Health Organization and, subsequently, practically all scientific societies recommended investigating AATD in all patients with COPD and in blood relatives of the index cases, as well as in other pathologies related to AATD, including bronchiectasis of unknown cause, neonatal cholestasis, liver cirrhosis of unknown cause, granulomatous polyangiitis, and neutrophilic panniculitis [1,2,32].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic considerations can also be raised, since, in selected cases, carriers of the PI*SZ genotype may be candidates for replacement therapy, as expressed in the Summary of Product Characteristics of the different approved ATs and in some guidelines [ 22 24 ]. In fact, recent data from the Spanish registry showed that 8.2% of registered PI*SZ individuals were receiving AT [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent data from the Spanish registry showed that 8.2% of registered PI*SZ individuals were receiving AT [ 25 ]. Again, if the risk for lung disease associated with PI*SS is not significantly different from that of PI*SZ, it may also be considered that some selected individuals with the PI*SS genotype could benefit from AT [ 22 , 23 ]. However, similar to PI*SZ, there is no evidence about the efficacy of AT in this population and the great majority (if not all) of subjects with the PI*SS genotype have serum levels above those considered to be protective [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…These approaches, however, need thorough evaluation and safety profiling before any first-in-man studies can be considered. Moreover, it remains controversial to suggest AAT augmentation therapy for asthma even though, conversely, individuals with AATD often demonstrate an increased prevalence of asthma [ 216 ]. Indeed, studies have shown AAT augmentation to not be any more efficacious in AATD individuals with asthma compared to those without; therefore, there is no evidence to indicate any significant impact of AAT augmentation on respiratory symptoms or exacerbations in asthma [ 216 ].…”
Section: Inhibition Of Allergen Serine Proteases As a Therapeutic Str...mentioning
confidence: 99%